Economic interests and regional trading arrangements : the case of NAFTA - Chase, Kerry A. (2003)
Reviews unresolved puzzles in the political economy of trading blocs. Presents an explanatory framework to examine the domestic politics of regional trade agreements. Tests these expectations on group preferences (lobbying in the United States) and policy outcomes (tariff-phasing schedules in the NAFTA treaty). Evaluates specific motives in U.S. domestic politics for regionalism and trade discrimination.